Changes to care delivery at nine international pediatric diabetes clinics in response to the COVID‐19 global pandemic. Issue 3 (16th February 2021) - Sarteau, Angelica Cristello; Souris, Katherine Janine; Wang, Jessica; Ramadan, Amira A.; Addala, Ananta; Bowlby, Deborah; Corathers, Sarah; Forsander, Gun; King, Bruce; Law, Jennifer R.; Liu, Wei; Malik, Faisal; et al.
Abstract: Background: Pediatric diabetes clinics around the world rapidly adapted care in response to COVID‐19. We explored provider perceptions of care delivery adaptations and challenges for providers and patients across nine international pediatric diabetes clinics. Methods: Providers in a quality improvement collaborative completed a questionnaire about clinic adaptations, including roles, care delivery methods, and provider and patient concerns and challenges. We employed a rapid analysis to identify main themes. Results: Providers described adaptations within multiple domains of care delivery, including provider roles and workload, clinical encounter and team meeting format, care delivery platforms, self‐management technology education, and patient‐provider data sharing. Providers reported concerns about potential negative impacts on patients from COVID‐19 and the clinical adaptations it required, including fears related to telemedicine efficacy, blood glucose and insulin pump/pen data sharing, and delayed care‐seeking. Particular concern was expressed about already vulnerable patients. Simultaneously, providers reported 'silver linings' of adaptations that they perceived as having potential to inform care and self‐management recommendations going forward, including time‐saving clinic processes, telemedicine, lifestyle changes compelled by COVID‐19, and improvements to family and clinic staff literacy around data sharing. Conclusions: Providers across diverse clinical settings reported care delivery adaptations in response to COVID‐19—particularly telemedicine processes—created challenges and opportunities to improve care quality and patient health. To develop quality care during COVID‐19, providers emphasized the importance of generating evidence about which in‐person or telemedicine processes were most beneficial for specific care scenarios, and incorporating the unique care needs of the most vulnerable patients.